Microbiological and physicochemical water quality assessments of river water in an industrial region of the northwest coast of Borneo - Leong, Sui Sien; Ismail, Johan; Ahmad Denil, Nurdiyana; Sarbini, Shahrul Razid; Wasli, Wafri; Lingoh, Arlene Debbie (MDPI, 2018)
Urbanization and ever increasing socioeconomic activities have degraded natural resources globally. This study monitored water quality (WQI) based on physicochemical and microbial qualities of river water in an industrial region northwest coast of Borneo. Microbiological parameters tested included total viable count (TVC), coliform count (TC), faecal coliform count (FC), and Escherichia coli confirmation. Physicochemical constituents evaluated included water temperatures (T), pH, total dissolved solids (TDS), salinity, electrical conductivity (EC), dissolved oxygen (DO), biochemical oxygen demand (BOD), ammoniacal nitrogen (NH3-N), chemical oxygen demand (COD) and total suspended solids (TSS). The mean microbial counts of samples were: TVC (3.9 × 102–3.0 × 104 cfu mL−1), TC and FC (23–>1600 MPN 100 mL−1) (MPN: the most probable number) and Escherichia coli growth was confirmed. The mean values of pH, TDS, salinity, EC and BOD are significantly different (p < 0.05) between the rivers ranged: pH (5.05 ± 0.03–6.10 ± 0.10), TDS (0.0 ± 0.0–38,600 ± 50 mg L−1), salinity (0.01 ± 0.0–3.07 ± 0.07%), EC (650 ± 25–19,566.67 ± 251.66 µS cm−1), and BOD (0.23 ± 0.10–3.12 ± 0.02 mgO2 L−1). The tested parameters of samples exceeded international limits with the exception of COD and TSS. The WQI of river water tested ranged from 65–73 under class III. Most of the river water was slightly polluted and a potential threat to public health.